New distribution patterns of Dirofilaria immitis in Italy - Napoli, Ettore; De Benedetto, Giovanni; Ciuca, Lavinia; Bosco, Antonio; Lia, Riccardo Paolo; Veneziano, Vincenzo; Bezerra Santos, Marcos Antônio; Otranto, Domenico; Rinaldi, Laura; Brianti, Emanuele (Frontiers in Veterinary Science, 2023)
In recent decades, the number of autochthonous cases and foci of Dirofilaria immitis in dogs from southern regions has increased considerably, suggesting that the distribution of the species is not limited to northern Italian regions. This epidemiological picture emerges from case reports or studies in specific locations where outbreaks of heartworm disease have occasionally been reported together with the presence of mosquito vectors. To obtain a more comprehensive picture of the current distribution of D. immitis in southern Italy, a multicenter cross-sectional survey of canine filariasis was conducted. Owned and sheltered dogs (n=1,987) were included in the survey regardless their breed, attitude and/or sex. All included dogs were older than 1 year and had no history of chemoprophylactic treatment against filarioses. A blood sample was collected from enrolled dogs and screened by Knott’s test and, when positive, further tested using a D. immitis specific ELISA antigen test. The overall microfilaremia prevalence was 17% (n=338) being single-species infection (92.6%) more common that mixed (7.4%). Remarkably, D. immitis was the most frequent species detected with an overall prevalence of 11.4% (n=227), followed by Dirofilaria repens (n=74; 3.7%) and Acanthocheilonema reconditum (n=12; 0.6%). Sheltered dogs were significantly more infected by D. immitis, as well as mongrel dogs and animals housed in rural areas. Data here reported indicate that D. immitis is largely present in southern Italy, raising awareness about the necessity of proper screening and chemoprophylactic treatments in exposed animals.